Media Talking Stick dalam Pembelajaran Maharah al-Kalam di MA Assunniyyah Jember - Imam Wahyudi; Siti Umi Azizatul Khofifah (An-Nuqthah, 2022)
Students sufficient speaking in Arabic is one indicator of mastery of Arabic. Therefore, knowledge of Arabic requires suitable learning media so that students are helped in learning it. Talking sticks can be one of the media that contributes to bring off students' Arabic speaking skills. This article schemed to check the achievement of the results of the media application in MA As-Sunniyyah Kencong Jember through qualitative research methods. The results afforded that students were reached good predicate in speaking skills based on assessment indicators with an average of 80.73, so the use of talking stick media can be said supporting students in achieving Arabic speaking skills.